Effect of Turmeric (Curcuma longa) Powder and Synbiotic as Alternative to Antibiotic Growth Promoter on Haemato-biochemical Parameters, Comparative Economics and Mortality of Broiler Chicks - Shende, Kavita; Dhuria, Rajesh Kumar; Meel, Mahendar; Nagar, Manish Kumar; Jediya, Hemant Kumar (International Journal of Bio-resource and Stress Management, 2021)
A study was conducted to investigate the effect of turmeric powder and synbiotic as alternative to antibiotic growth promoter on haemato-biochemical parameters, comparative economics and mortality of broiler chicks. Total 150 day-old chicks were randomly divided into 5 treatments having 30 chicks in each group with three replicates of 10 chicks in each. Control group was fed basal diet, second group supplemented with antibiotic @ 0.02%, third supplemented with turmeric @ 0.5%, fourth supplemented with synbiotic @ 0.05% and fifth supplemented with turmeric @ 0.25%+synbiotic @ 0.025% in the diet. Haemato-biological parameters, comparative economics and mortality were recorded. Non-significant (p>0.05) effect was observed for haemato-biochemical parameters. However, numerically highest level of haemoglobin, packed cell volume, total protein, albumin and globulin was found in group supplemented with turmeric and synbiotic powder in combination. Highest reduction in serum triglyceride and cholesterol level was observed in group supplemented with turmeric and synbiotic powder in combination and lowest reduction was observed in control group. Highest net return per bird was observed in group supplemented with turmeric and synbiotic powder in combination and lowest was observed in control group. Lowest mortality was observed in a group supplemented with turmeric and combination group, while highest mortality was observed in control group. It can be concluded that as an alternative to antibiotics, addition of turmeric and synbiotic combination in the diets positively influenced haemato-biochemical parameters and comparative economics with reduced mortality of broiler.